(untitled) (KULT_online, 2021)
Superfluous Women: Art, Feminism, and Revolution in Twenty-First-Century Ukraine is an archive showcasing the entanglements between “the vanguard” (p. 5) of the 2000s’ Ukraine, the state, and revolution. Jessica Zychowicz makes an invaluable contribution to the anglophone study of Ukrainian feminist protest and the cultural dissensus about Soviet heritage and post-Maidan state politics. The cultural production considered in Superfluous Women highlights both the ambivalence of Ukrainian society and the failures of the state’s attempts to sustain a “monopoly on ‘truth’” (p. 264).